The Influence of the TGT Model Assisted by the Plickers Application Media on Understanding Mathematical Concepts - Elwan Stiadi (Universitas Bengkulu, 2025)
This study aims to analyze the effect of the Teams Games Tournament (TGT) learning model assisted by the Plickers application media on the understanding of mathematical concepts of second-semester students of the Bachelor of Mathematics Education, University of Bengkulu. This type of research is a quasi-experimental study with a non-equivalent pretest-posttest control group design. The population in this study were all second-semester students of the Bachelor of Mathematics Education, University of Bengkulu in the 2023/2024 academic year. The sample of this study was taken using a purposive sampling technique where 30 students from the second semester of Class A were taught using the Teams Games Tournament (TGT) model assisted by the Plickers application and 32 students from the second semester of Class B were taught using the direct learning model. Data collection was carried out using a mathematical concept ability test instrument. The results of the hypothesis test showed that the sig value (2-tailed) was 0.000 <significant level (α) = 0.05 and supported by an N-Gain of 0.581 with a moderate category. Therefore, it can be concluded that there is a significant influence of the Teams Games Tournament model assisted by the Plickers application media on the mathematical concept understanding ability of 2nd semester students of the Bachelor of Mathematics Education program at the University of Bengkulu.